2017
DOI: 10.1089/pho.2017.4279
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Photobiomodulation Delivered by Light-Emitting Diode on Stem Cells from Human Exfoliated Deciduous Teeth: A Study on the Relevance to Pluripotent Stem Cell Viability and Proliferation

Abstract: LED irradiation at 630 nm (37 mW/cm, 75 mW) with radiant exposure of 16 J/cm was capable of inducing a proliferative response in stem cells from the pulp tissue of deciduous teeth without affecting mitochondrial function or inducing senescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…All the studies analyzed showed qualitative and quantitative different parameters and for this reason it is very difficult to compare them and to identify a univocal protocol. Nearly all papers showed that LLLT had a positive effect on HPDLSCs, hDPSCs, hBMSCs and hADSCs proliferation with doses used between 0.5 and 10 J/cm 2 , while doses higher than 10 J/cm 2 exert or no effects [7] or seems to be antiproliferative [93] and similar outcomes were found for LED [104]. In addition, no study showed deleterious effects of LLLT on these cells [105].…”
Section: Discussionmentioning
confidence: 85%
“…All the studies analyzed showed qualitative and quantitative different parameters and for this reason it is very difficult to compare them and to identify a univocal protocol. Nearly all papers showed that LLLT had a positive effect on HPDLSCs, hDPSCs, hBMSCs and hADSCs proliferation with doses used between 0.5 and 10 J/cm 2 , while doses higher than 10 J/cm 2 exert or no effects [7] or seems to be antiproliferative [93] and similar outcomes were found for LED [104]. In addition, no study showed deleterious effects of LLLT on these cells [105].…”
Section: Discussionmentioning
confidence: 85%
“…A previous study by Vale et al . (34) found genomic DNA damage when a single LED irradiation of 4 J cm −2 was applied in MSCs. It is worth mentioning that the irradiance used by the researchers was 37 mW cm −2 for 1 min and 47 s, more than twice the irradiance employed in our experimental set and for less than twice the irradiation time.…”
Section: Discussionmentioning
confidence: 99%
“…Tani et al [44] reported that proliferation and osteogenic differentiation is increased at 635 nm of wavelength in in vitro study. Not only other studies focus on the osteogenetic effects of PBM [45][46][47][48][49], but also Peat et al [50] reported that PBM therapy using neodymium-doped yttrium aluminum garnet laser at 1,064 nm can enhance the angiogenesis which can promote the bone healing. Furthermore, in osteogenic aspects, LLLT irradiation (gallium-aluminumarsenide diode; λ 830 nm, 30 mW, θ 1 mm) showed almost two-times greater bone formation rate with new bone structural unit in histometric analysis (13.29% vs. 26.17%).…”
Section: Photobiomodulation Therapy For Bone Regenerationmentioning
confidence: 99%